Real sample application. (a) Reusability studies of 100 mg of Fe3O4/PS composites in terms of removal efficiency changes for the capturing properties of 15 mg/L of MB after five regeneration/reuse cycles, (b) Selectivity of Fe3O4/PS composite toward MB in the presence of the MO ionic dye, and (c) monitoring of MB in industrial wastewater samples. - Tamer S. Saleh (5181146) (2025)
Real sample application. (a) Reusability studies of 100 mg of Fe3O4/PS composites in terms of removal efficiency changes for the capturing properties of 15 mg/L of MB after five regeneration/reuse cycles, (b) Selectivity of Fe3O4/PS composite toward MB in the presence of the MO ionic dye, and (c) monitoring of MB in industrial wastewater samples.